Pattern Recognition and Machine Intelligence 8th International Conference, PReMI 2019, Tezpur, India, December 17-20, 2019, Proceedings, Part II - Deka, Bhabesh; Maji, Pradipta; Mitra, Sushmita; Bhattacharyya, Dhruba Kumar; Bora, Prabin Kumar; Pal, Sankar Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The two-volume set of LNCS 11941 and 11942 constitutes the refereed proceedings of the 8th International Conference on Pattern Recognition and Machine Intelligence, PReMI 2019, held in Tezpur, India, in December 2019. The 131 revised full papers presented were carefully reviewed and selected from 341 submissions. They are organized in topical sections named: Pattern Recognition; Machine Learning; Deep Learning; Soft and Evolutionary Computing; Image Processing; Medical Image Processing; Bioinformatics and Biomedical Signal Processing; Information Retrieval; Remote Sensing; Signal and Video Processing; and Smart and Intelligent Sensors.
Pattern Recognition -- Machine Learning -- Deep Learning -- Soft and Evolutionary Computing -- Image Processing.-Medical Image Processing -- Bioinformatics and Biomedical Signal Processing -- Information Retrieval -- Remote Sensing -- Signal and Video Processing -- Smart and Intelligent Sensors.
Keywords: Computer science; Artificial intelligence; Computer vision; Information storage and retrieval systems; Data mining; 9; Theory of Computation; Artificial Intelligence; Computer Vision; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Computer Communication Networks